High quantum yield and pH sensitive fluorescence dyes based on coumarin derivatives: fluorescence characteristics and theoretical study. Issue 54 (18th May 2016) - Hua, Chao-jun; Zhang, Kan; Xin, Ming; Ying, Ting; Gao, Jian-rong; Jia, Jian-hong; Li, Yu-jin
Abstract : The fluorescence coumarin derivatives were synthesized by an efficient one-pot, three-component reaction in 80–90% yields. Abstract : The fluorescence coumarin derivatives were synthesized by an efficient one-pot, three-component reaction in 80–90% yields. These fluorescence dyes exhibited high fluorescent intensity and quantum yield where compound4e, with p -methyl substituted on the phenyl ring, had the maximum fluorescence intensity and also the fluorescence quantum yield reached 0.83. These coumarin derivatives display different fluorescence in acidity and alkaline conditions and the fluorescent colour changed from blue to yellow-green when the pH of the solution turned from acidic to alkaline. The pH sensitive fluorescence properties of the coumarin derivatives showed a large shift from 441 to 538 nm in wavelength. Experimental results were confirmed with DFT and TDDFT calculations.